Use of the STAR PROCESS for Children with Sensory Processing Challenges - Sarah A. Schoen; Lucy Jane Miller; Stephen Camarata; Andrea Valdez (Scholarworks @ WMU, 2019)
Background: This study examined the effectiveness of the STAR PROCESS, an intensive, short-term intervention that combines principles of sensory integration, relationship-based therapy, and parental-therapist collaboration for children with sensory processing challenges. Method: A nonconcurrent multiple baseline, repeated measures design was used. Four boys, aged 5 years 0 months to 7 years 9 months, participated in this study. The mean length of intervention was 22 sessions delivered 3 to 5 times per week. A behavioral coding system was used to measure change in four areas: play level, positive affect, joint attention, and novel use of equipment. The theory of change reflects the use of multisensory experiences in combination with parent participation to impact outcomes. Results: Improvement was noted in play level in all of the participants. Multisensory experiences and parent participation were associated with these changes in two participants. Discussion: The study results suggest a feasible methodology to study occupational therapy interventions. The behavioral coding system was sensitive to change. Play abilities changed in all four children. Preliminary support was provided for the theory of change combining multisensory experiences with parent participation. Conclusion: A targeted treatment approach that emphasizes parents as play partners in a multisensory environment shows promise in remediating these deficits.